Grandfather rights in the market for airport slots - Gernot Sieg (Technische Universität Braunschweig, Institut für Volkswirtschaftslehre, 2009)
Grandfather rights are currently used in the European Union to allocate airport slots. This article shows that airports prefer such a use-it-or-lose-it rule to unconditional property rights. Assuming that there are informational asymmetries between airports and air carriers because air carriers have better information on passenger demand, the use-it-or-lose-it rule increases slot use when demand for air transport is low. Airport prots increase and those of the air carriers, together with social welfare, decrease. The prot-maximizing rule is a use-it- g < 1-or-lose-it rule.
urn:nbn:de:gbv:084-24464
Keywords: L93; R48; D42; 330; Airports; Grandfather rights; use-it-or-lose-it rule; airport slots